2016
DOI: 10.1037/pas0000278
|View full text |Cite
|
Sign up to set email alerts
|

Interrater reliability of Violence Risk Appraisal Guide scores provided in Canadian criminal proceedings.

Abstract: Published research suggests that most violence risk assessment tools have relatively high levels of interrater reliability, but recent evidence of inconsistent scores among forensic examiners in adversarial settings raises concerns about the "field reliability" of such measures. This study specifically examined the reliability of Violence Risk Appraisal Guide (VRAG) scores in Canadian criminal cases identified in the legal database, LexisNexis. Over 250 reported cases were located that made mention of the VRAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Tools like FoVOx show similar or better performance to other tools, but are easier, quicker, and free to use whilst at the same time being scalable, fully transparent, and less subjective. Additionally, while measures of interrater reliability of structured clinical judgement tools are generally high in research settings [45] , this may not be the case when used in adversarial settings [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Tools like FoVOx show similar or better performance to other tools, but are easier, quicker, and free to use whilst at the same time being scalable, fully transparent, and less subjective. Additionally, while measures of interrater reliability of structured clinical judgement tools are generally high in research settings [45] , this may not be the case when used in adversarial settings [46] .…”
Section: Discussionmentioning
confidence: 99%
“…This was not possible with the current dataset, as only four decisions included actual raw scores and only one case included scores from more than one evaluator. The differences in available data are probably due to the restricted time frame of the current study (compared with Edens et al, ) and the jurisdictional differences (Edens et al reviewed Canadian case law only). Nonetheless, Edens et al () reported lower than expected intraclass correlations, with rater disagreement strongly predicted by a single VRAG item, the offender's PCL‐R score.…”
Section: Discussionmentioning
confidence: 71%
“…The differences in available data are probably due to the restricted time frame of the current study (compared with Edens et al, ) and the jurisdictional differences (Edens et al reviewed Canadian case law only). Nonetheless, Edens et al () reported lower than expected intraclass correlations, with rater disagreement strongly predicted by a single VRAG item, the offender's PCL‐R score. This item was altered in a revised version of the measure (Rice, Harris, & Lang, ) and, although it is unlikely that this revision would impact the application and communication of the VRAG, more research examining score reliability across setting and evaluators is warranted.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations